Antineoplastic effects of targeting CCR5 and its therapeutic potential for colorectal cancer liver metastasis - Pervaiz, Asim; Zepp, Michael; Georges, Rania; Bergmann, Frank; Mahmood, Saqib; Faiza, Syeda; Berger, Martin R.; Adwan, Hassan (Journal of cancer research and clinical oncology, 2021)
Liver metastasis is observed in up to 50% of colorectal cancer (CRC) patients. Available treatment options are limited and disease recurrence is often. Chemokine receptor 5 (CCR5) has attracted attention as novel therapeutic target for treating cancers. In this study, we reinforced the importance of CCR5 as therapeutic target in CRC and its liver metastasis by applying in vitro, in vivo and clinical investigations.